Parametric finite element investigation of the critical load capacity of elastomeric strip bearings - Warn, Gordon P.; Weisman, Jared (Engineering structures, 2011)
Elastomeric bearings are used in non-seismic bridge applications and for seismic isolation of structures. These bearings consist of a number of elastomeric (rubber) layers bonded to intermediate steel shim plates. For seismic isolation, the total thickness of rubber provides a low horizontal stiffness, whereas the close spacing of the intermediate shim plates provides a high vertical stiffness, relative to the horizontal, for a given bonded rubber area and shear modulus. During earthquake ground shaking, large lateral displacements will develop across the isolation interface and the individual bearings. The design of elastomeric bearings for seismic isolation requires that the stability of the individual bearings be demonstrated at the maximum bearing displacement. A component of the stability assessment is the determination of the critical load of the bearing at a given lateral displacement. Currently, the critical load is estimated using an approach whereby a ratio, that of the overlapping area between the top and bottom bearing endplates to the bonded rubber area, is used to reduce the critical load at zero lateral displacement, referred to herein as the overlapping area method. This study verifies the finite element method for predicting critical loads in elastomeric bearings, and uses the finite element method to investigate the dependency of the critical load on the bearing geometry. The results of the parametric study were also used to evaluate the predictive capabilities of the overlapping area procedure. ► The critical load capacity of elastomeric strip bearings is investigated. ► Critical load predictions from a finite element model were experimentally verified. ► A parametric finite element study of elastomeric strip bearings was performed. ► The sensitivity of the critical load to various geometric parameters is assessed. ► The critical load capacity is sensitive to the individual rubber layer thickness.